Oncology education in Brazilian medical schools - Nogueira-Rodrigues, Angelica; Albuquerque, Ronniel Morais; Clara, Renan Orsati; Gelatti, Ana; Mota, Augusto Cesar de Andrade; Pereira, Bruno Pacheco; Rosa, Daniela Dornelles; Morbeck, Igor Alexandre Protzner; Gaui, Maria Fátima; Melro-Braghiroli, Maria Ignez Freitas; Kaliks, Rafael Aliosha; Munhoz, Rodrigo Ramella; Cavalléro, Sandro Roberto de Araújo; Cordeiro-de-Lima, Vladmir Cláudio; Mathias, Clarissa Maria de Cerqueira (Brazilian Journal of Oncology, 2020)
Background and Objective: Cancer is expected to be the leading cause of death in Brazil by 2030. This scenario demands that health professionals, especially physicians, should be able to implement primary prevention, early detection and cancer patient support. Despite this unquestionable need, there is a clear gap in Oncology training of Brazilian medical students. The aim of the current analysis is to delineate the Oncology education scenario in Brazilian medical schools. Methods: A descriptive review of the curricular program and pedagogical plan of medical schools in Brazil was carried out. We evaluated Oncology discipline offer in Brazilian medical schools. Data were analyzed and characterized for variables of interest. A geo-referenced mapping was done for a graphic projection of the oncology discipline distribution throughout the country. Results: 254 out of the 345 medical schools registered in Brazil in 2019 were analyzed. 41.3% of the Brazilian medical schools offer Oncology discipline in their medical curriculum, being 86.7% obligatory (average workload 57h), and 13.3% optional (average workload 48h). Oncology discipline offer is higher in public medical schools, and in the Southeast (45.7%) and South (22.9%) regions. There is limited access to oncology education in regions where preventable cancers incidence is higher, as the North and Northeast Brazilian regions. Conclusion: There is an alarming gap in Oncology training in Brazilian medical schools, and tackling this issue is essential to advance cancer control in the country.
Keywords: Oncology education; Brazilian Medical schools